2010
DOI: 10.1016/j.neuron.2010.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations and Filtering Networks Support Flexible Routing of Information

Abstract: SummaryThe mammalian brain exhibits profuse interregional connectivity. How information flow is rapidly and flexibly switched among connected areas remains poorly understood. Task-dependent changes in the power and interregion coherence of network oscillations suggest that such oscillations play a role in signal routing. We show that switching one of several convergent pathways from an asynchronous to an oscillatory state allows accurate selective transmission of population-coded information, which can be extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
253
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(264 citation statements)
references
References 67 publications
10
253
0
1
Order By: Relevance
“…3b). The observation that mid-and high-gamma activity were related to the phase consistency of beta and theta activity, respectively, extends the ideas that gamma frequency variations reflect information routing 32,34,45,46 and that message-passing is indexed by specific hierarchical combinations of slow and high frequencies (low/high frequency ratio) 47 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…3b). The observation that mid-and high-gamma activity were related to the phase consistency of beta and theta activity, respectively, extends the ideas that gamma frequency variations reflect information routing 32,34,45,46 and that message-passing is indexed by specific hierarchical combinations of slow and high frequencies (low/high frequency ratio) 47 .…”
Section: Discussionsupporting
confidence: 68%
“…3b). The observation that mid-and high-gamma activity were related to the phase consistency of beta and theta activity, respectively, extends the ideas that gamma frequency variations reflect information routing 32,34,45,46 and that message-passing is indexed by specific hierarchical combinations of slow and high frequencies (low/high frequency ratio) 47 .The current data demonstrate that violating intermodal expectations changes the neural dynamics of slow (delta and theta) brain activity, and increases the coordination between local low-beta and high-gamma oscillatory activity. Our data suggest that this transition occurs in brain regions where audio-visual predictions are likely updated (STS) and new prediction errors generated (auditory and visual cortices).…”
supporting
confidence: 70%
“…S5), indicating that patterns of phase differences should not be confused with patterns of directed connectivity or, indeed, information flow. Instead, one could hypothesize that the net outflow of information from posterior regions is due to an increase in encoded information at higher firing rates (52), as simulations have shown that hubs also possess the highest levels of neuronal activity in the network, that is, the highest firing rates (53) and the highest power (22,53).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, modeling work suggests that the relationship between power and directionality may not simply be caused by differences in SNR but may be due to a neuronal mechanism that drives this correlation (52). Akam and Kullmann (52) showed that the amount of synchronous activity in a sending neuronal population, reflected in the amplitude of oscillations, is strongly related to the amount of information available to the receiving neuronal population. At the same time, interneuron motifs within the receiving neuronal population can act as bandpass filters to selectively gate incoming signals.…”
Section: Discussionmentioning
confidence: 99%
“…Granule cells and their surrounding interneurons are tuned to respond differentially to particular oscillatory frequencies of input from EC [110], hence the net impact of PP input on GC firing could be adaptively filtered according to its pattern and does not depend solely on excitation. Models suggest that filtering of this kind by dynamically tuned inhibition may be used to divert information via different routes during different behavioral states [111,112]. For example, novelty induces a significant increase in the firing rates of inhibitory interneurons in the DG and a slight decrease in granule cell firing rates [113].…”
Section: Box3: Inhibitory Influencesmentioning
confidence: 99%